2022
DOI: 10.3389/fmed.2022.928468
|View full text |Cite
|
Sign up to set email alerts
|

Jinhua Qinggan granules for non-hospitalized COVID-19 patients: A double-blind, placebo-controlled, and randomized controlled trial

Abstract: BackgroundKey findings from the World Health Organization Expert Meeting on Evaluation of Traditional Chinese Medicine (TCM) in treating coronavirus disease 2019 (COVID-19) reported that TCMs are beneficial, particularly for mild-to-moderate cases. The efficacy of Jinhua Qinggan granules (JHQG) in COVID-19 patients with mild symptoms has yet to be clearly defined.MethodsWe conducted a phase 2/3, double-blind, randomized, placebo-controlled trial to evaluate the efficacy and safety of treatment with JHQG in mil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The results from the included studies [ 15 17 , 24 ] yielded a combined sample size of 582 patients. Of the 4 studies, one was conducted in Pakistan and the remainder in China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the included studies [ 15 17 , 24 ] yielded a combined sample size of 582 patients. Of the 4 studies, one was conducted in Pakistan and the remainder in China.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 15 , 17 , 24 ] were included to report the effect of Jinhua Qinggan granules on the rate at which COVID-19 patients resumed testing negative for SARS-COV-2 nucleic acids. The meta-analysis results of the random effects model showed that there was no statistically significant difference between the 2 groups [RR = 1.31, 95% CI (0.63, 2.71), P = .47] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese studies have shown that TCM treatment combined with western medicines has an encouraging therapeutic effect on COVID-19 patients ( Huang et al, 2021 ; Ni et al, 2020 ; Shah et al, 2022 ; Zhu et al, 2022 ). The main principle of TCM theory in treating infectious diseases is strengthening the body's resistance to eliminate pathogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al conducted a phase 2/3, double-blind, randomized, placebo-controlled trial to evaluate the efficacy and safety of treatment with Jinhua Qinggan granules in non-hospitalized patients with laboratoryconfirmed mild COVID-19 (28). They found that Jinhua Qinggan granules displayed better clinical efficacy (82.67%) compared to a placebo (10.74%), and the recovery time from symptoms such as a cough, phlegm, a sore throat, and headaches in patients receiving Jinhua Qinggan granules was shorter than that in patients receiving a placebo (6 days vs. more than 11 days).…”
Section: Jinhua Qinggan Granulesmentioning
confidence: 99%